Contamination of Computer Keyboards in Various Wards of Vali-e Asr Teaching Hospital in Birjand, Iran - Seyed Alireza Javadinia; Nahid Askari; Hoda Khoshbakht; Sima Surgi; Mohammad Hasan Namaei (Tehran University of Medical Sciences, 2012)
Background and Aim: The aim of this study was to evaluate bacterial contamination of keyboards of computers located in various wards of Vali-e Asr Teaching Hospital, Birjand, Iran. Materials and Methods: In this study, all computer keyboards in various wards of Vali-e Asr Hospital were sampled (n=24). Then, the samples were sent to Microbiology Research Laboratory at Birjand University of Medical Sciences and were cultured on Blood ager, Manitol Salt ager and Eosin Methylene Blue media. The isolated bacteria were identified based on their colonial morphology and biochemical characteristics. Results: A total of 26 samples from 24 different computer keyboards of 16 different wards were obtained. Two keyboards of Infectious Diseases and Neurology wards were routinely disinfected at the end of every shift. All samples(100%) showed contamination to different bacteria. The keyboard of the computer located in Internal Medicine ward(womens division) was the most contaminated one. In total, 13 different bacterial spp. were isolated from keyboards of different computers. The species belonging to Enterobacteriaceae family(61.5%) were the most common contaminating bacteria followed by Bacillus spp(30.7%). Conclusion: Based on the results, all the sampled keyboards were contaminated by at least one bacterial spp. Therefore, it is necessary to pay more attention to the fact that computer keyboards in hospitals should regularly be disinfected.